Validation of a scale to evaluate Digital Dependence of Employees - Gonçalves,Lucio Lage (2019)
BACKGROUND: The evolution of technologies and mobility, new digital resources have emerged transforming human behavior. These include the abusive use of digital devices, leading to various dependences regarding the way people use technology. Collective environments also begin to exhibit symptoms of such dependences. OBJECTIVE: Validate a Digital Dependence of Employees Scale (DDES), applied to personnel not holding leadership positions in organizations. METHOD: Data were collected via Internet. The sample totaled 301 volunteers from a state-owned company, of which 294 were statistically validated. Participants were asked to answer 20 questions prepared by experts. After the collection procedure, a database was created for statistical analysis. RESULTS: Statistical analysis procedure including factorial analysis was conducted, which confirmed data adequacy. Three statistical criteria were used: Bartlett Sphericity test, Kaiser-Meyer-Olkin Criterion and Factorial analysis, including Screeplot; the latter determined adequate commonalities, indicating the cancellation of only 1 out of the 20 original scale questions. The internal consistency of the scale measured through the Cronbach Alpha Coefficient showed a positive result of 0.764. Thus, scale validation objectives were achieved. CONCLUSION: The DDES scale was considered validated to be applied to employees in organizational environments. The limitations found to apply the scale did not compromise its results.